Pemesinan Paduan Ti-6Al-4V ELI - Ibrahim, Gusri Akhyar; Saputra, endra (TURBO [Tulisan Riset Berbasis Online], 2023)
Titanium alloy material Ti-6Al-4V ELI (Extra Low Interstitial) is a type of alloy that has very similar properties to Ti-6Al-4V (Grade 5) alloy, which is the most widely used material, but only differs in terms of properties. his tenacity. Ti-6Al-4V ELI has higher ductility and better fracture toughness. In addition, this material also has a good ability to work at high temperatures without losing its main properties. The main properties of this material are corrosion toughness at high temperatures and excellent weight to strength ratio. Referring to these advantages, the alloy material of the Ti-6Al-4V ELI type has been developed in many fields including the field of planting materials in the medical field, the aircraft industry, applications in the field of military weapons, the manufacture of racing vehicle components and also high pressure vessels for storing materials. low-temperature (cryogenic) liquid nitrogen [16].. During the machining process of titanium alloy, many things become obstacles because this material is a material that is difficult to machine. This is because the titanium alloy has high hardness, there is often a reaction between the cutting tool and the workpiece material during the cutting process, and there is an accumulation of high temperatures in the cutting area. Factors cutting speed and feed rate are the two dominant factors on the formation of cutting tool wear, both wear on the face or crater side. Damage to the cutting tool is also followed by damage to the surface of the workpiece being machined or the surface quality of the workpiece. The dominant wear that occurs in the rib face area is wear due to adhesion, notch wear, while wear in the crater area is diffusion that occurs during the machining process. Meanwhile, the cutting temperature has a direct impact on the surface quality of the workpiece being machined. The factor of high cutting speed with low feed rate is a combination of factors that provide good cutting force. Meanwhile, insert type cutting tools that have a hard coating, such as TiN, TiAlN and TiCrN play a significant role in the formation of tool wear. Likewise, hard coated tools provide better performance compared to uncoated insert tools. Machining with the Minimum Quantity Lubrication (MQL) method gives better results compared to dry machining and machining using flooded cooling.Keywords: machining, Ti-6Al-4V ELI, cutting tool, materials.